2022
DOI: 10.3390/antibiotics11060738
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical, Microbiological and Immunological Results of Local Doxycycline or Antimicrobial Photodynamic Therapy for Recurrent/Persisting Periodontal Pockets: A Randomized Clinical Trial

Abstract: We evaluated, in this study, the clinical, microbiological and immunological effects of local drug delivery (LDD) or photodynamic therapy (PDT), adjunctive to subgingival instrumentation (SI) in persistent or recurrent periodontal pockets in patients enrolled in supportive periodontal therapy (SPT) after one year. A total of 105 patients enrolled in SPT with persistent/recurrent pockets were randomly treated with SI +PDT or SI + LDD or SI (control). The number of treated sites with bleeding on probing (n BOP+)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…found that repeated PDT could reduce A. actinomycetemcomitans , Tannerella forsythia , and T. denticola in 4–6‐mm pockets and T. denticola in pockets >6 mm at 6 months. However, in a long‐term study, no significant reduction of periodontopathogens was observed in the group that accepted one time of PDT 47 . In our study, repeated PDT showed a more durable and powerful effect than single PDT.…”
Section: Discussioncontrasting
confidence: 63%
“…found that repeated PDT could reduce A. actinomycetemcomitans , Tannerella forsythia , and T. denticola in 4–6‐mm pockets and T. denticola in pockets >6 mm at 6 months. However, in a long‐term study, no significant reduction of periodontopathogens was observed in the group that accepted one time of PDT 47 . In our study, repeated PDT showed a more durable and powerful effect than single PDT.…”
Section: Discussioncontrasting
confidence: 63%
“…This excited photosensitizer, possessing a longer life-time compared to ordinary reactive oxygen species (ROS), interacts with the surrounding molecules. In its triplet state, a cascade of reactions occur, leading to the generation of cytotoxic species [ 33 , 34 ]. Two distinct pathways have been proposed for the reactions of the triplet state: Type I and Type II [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These free-radical species further interact with endogenous molecular oxygen, resulting in the production of highly reactive oxygen species, including superoxide, hydroxyl radicals, and hydrogen peroxide. These reactive oxygen species essentially “attack” the cell membrane, causing its disintegration and leading to irreversible biological damage [ 23 , 33 , 34 ]. On the other hand, Type II reaction involves the direct interaction of the triplet state photosensitizer with molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Among the photosensitizers examined in research involving Pg , the most extensively studied to date have been indocyanine green [ 91 , 92 , 93 ], methylene blue [ 94 , 95 , 96 ] and toluidine blue [ 97 , 98 , 99 ]. Other photosensitizers have included: aminolevulinic acid [ 100 ], azulene [ 101 ], β-NaYF 4 :Yb 3+ , Tm 3+ @TiO 2 (termed UCNPs@TiO 2 ) [ 102 ], BLC 1010 and BLC 1014 [ 103 ], cadmium telluride nanocrystals [ 104 ], captopril-protected gold clusters [ 105 ], cationic amino acid-porphyrin conjugate 4i [ 106 ], Chlorin-e6 [ 103 , 107 , 108 ], chloro-aluminum phthalocyanine [ 109 , 110 ], Coumarin 6 [ 111 ], Curcumin [ 112 , 113 ], curcumin-NP [ 114 ], cyanidin-3-glucoside [ 115 ], doxycycline [ 116 ], erythrosine [ 115 , 117 ], graphene silver polymethyl methacrylate [ 118 ], lysine-porphyrin conjugate 4i [ 119 ], meta-tetra(hydroxyphenyl)chlorin (mTHPC) [ 120 ], oxyhemoglobin-based oxyHb@IR820 [ 121 ], phenothiazine chloride [ 122 , 123 , 124 ], phloxine B [ 125 ], Photodithazine [ 126 ], phycocyanin [ 127 ], protoporphyrin IX [ 35 ], purpurin-based photosensitizer [ 128 ], Radac...…”
Section: Mode 5: Cell Lysis Through Drug/light Interaction (Apdt)mentioning
confidence: 99%